Drug-induced falls in older persons: is there a role for therapeutic drug monitoring?. (April 2016) - Hartholt, Klaas A.; Becker, Matthijs L.; van der Cammen, Tischa J. M.
Background: Falls are the leading cause of injuries among older persons. Because of ageing societies worldwide, falls are expected to become a prominent public health problem. The usage of several types of drugs has been associated with an increased fall and fracture risk. In order to reduce future falls, preventative measures are needed. Therapeutic drug monitoring may help to identify persons who are at risk for falls due to drug use. The aim was to demonstrate how drugs can contribute to falls and the role of therapeutic drug monitoring. Methods: We present a descriptive case series of four patients. Results: All patients were referred to the geriatric outpatient clinic of a university medical center. The presented cases contained different underlying mechanisms contributing to an increased fall risk in older adults, including renal failure, genetic variation, overdose and ageing. Conclusion/discussion: Older adults are more prone to the side effects of drug use, including falls. Therapeutic drug monitoring may be useful to identify the patients who have an increased drug-related fall risk and to prevent future falls by individualizing the drug regime.